International railroads and human mobility controls at the Franco-Belgian border (1840s-1860s) - Torsten Feys (Diasporas: Circulations, Migrations, Histoire)
The article analyses how international railroad connections affected controls of cross-border mobility at the Franco-Belgian border. It refutes the idea that railroads made an end to these controls. Conversely it shows how the Sûreté publique continued to rely on border checks while developing means of monitoring foreigners in the interior. The article highlights that the Sûreté developed into a well-oiled information gathering machine, which allowed it to coordinate the expulsion of whom it deemed undesirable. Railroads greatly facilitated these expulsions toward a limited amount of border points. This infrastructure allowed expulsion to become a central pillar of Belgium’s migration policies.